2018
DOI: 10.1002/anie.201802055
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Fluorine‐Doped Carbon Electrocatalyst for CO2 Reduction Outcompeting Hydrogen Evolution

Abstract: The electrochemical CO reduction (ECDRR), as a key reaction in artificial photosynthesis to implement renewable energy conversion/storage, has been inhibited by the low efficiency and high costs of the electrocatalysts. Herein, we synthesize a fluorine-doped carbon (FC) catalyst by pyrolyzing commercial BP 2000 with a fluorine source, enabling a highly selective CO -to-CO conversion with a maximum Faradaic efficiency of 90 % at a low overpotential of 510 mV and a small Tafel slope of 81 mV dec , outcompeting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
139
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(146 citation statements)
references
References 38 publications
4
139
0
2
Order By: Relevance
“…[20,31] We hypothesize that the doped species within NSHCF is the origin of the disparity in the catalytic activity (for example,N -doped carbons have excellent CO 2 RR capabilities). [17] As calculation results shown in Figure 3b,t he lower Gibbs free energy barrier of 1.01 eV for *COOH occurs at pyridinic N adjacent to carbon-bonded Sa tom, consistent with 105 mV dec À1 Tafel slope and 94 %F aradaic efficiencyo f CO at À0.7 V RHE using NSHCF900. DFT calculations based on the structure model in the Supporting Information, Figure S17 and Table S2 were conducted to further explore the possible role of nitrogen-and sulfur-doping played in CO 2 RR.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…[20,31] We hypothesize that the doped species within NSHCF is the origin of the disparity in the catalytic activity (for example,N -doped carbons have excellent CO 2 RR capabilities). [17] As calculation results shown in Figure 3b,t he lower Gibbs free energy barrier of 1.01 eV for *COOH occurs at pyridinic N adjacent to carbon-bonded Sa tom, consistent with 105 mV dec À1 Tafel slope and 94 %F aradaic efficiencyo f CO at À0.7 V RHE using NSHCF900. DFT calculations based on the structure model in the Supporting Information, Figure S17 and Table S2 were conducted to further explore the possible role of nitrogen-and sulfur-doping played in CO 2 RR.…”
supporting
confidence: 76%
“…[16,17] Recently,n anostructured carbon materials have emerged as alternative electrocatalysts to metal-and metal oxide-based counterparts for CO 2 RR. [16,17] Recently,n anostructured carbon materials have emerged as alternative electrocatalysts to metal-and metal oxide-based counterparts for CO 2 RR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its large specific surface area is beneficial to the diffusion kinetics of lithium ions and enables electrochemical storage and release of high‐density energy . F‐doped carbon can also be used as an efficient catalyst for electrochemical CO 2 reduction, in which the incorporation of F can activate adjacent C atoms and facilitate the catalytic reactions …”
Section: Introductionmentioning
confidence: 99%
“…Figure S19 indicated that the EPR signal for BIF-29 decrease in density with irradiation time under nitrogen atmosphere.A sacomparison, the EPR signal of Icoordinated BIF-33 keep nearly unchanged. [25] In addition, from the density of states of two models,itisfound that BIF-29 without I À delivers anew state in the conduction band near the Fermi level (Figure 3d), indicating enhanced reactivity in BIF-29 compared to the BIF-33. [20] Furthermore,w hen CO 2 is introduced, the EPR signal of BIF-29 exhibit slightly changed with irradiation time,s uggesting that the trapped electrons on Cu sites can be further transferred to the adsorbed CO 2 molecules on the catalytic sites.…”
mentioning
confidence: 99%